Part-Metric and Its Applications to Cyclic Discrete Dynamic Systems - Wanping Liu; Xiaofan Yang; Stevo Stević; Bratislav Iricanin (Abstract and Applied Analysis)
We adapt the part metric and use it in studying positive solutions of a certain family of discrete dynamic systems. Some examples are presented, and we also compare some results in the literature.